2022
DOI: 10.3390/v14040782
|View full text |Cite
|
Sign up to set email alerts
|

Two Years and Four Time Points: Description of Emotional State and Coping Strategies of French University Students during the COVID-19 Pandemic

Abstract: While it is now clear that the COVID-19 pandemic has had a major impact on the mental health of individuals, especially the most vulnerable ones such as students, we have very little knowledge about the long-term consequences. The objective of this study was to compare the mental health and coping of French university students during the different phases of the pandemic in the first 2 years. To this end, French university students were evaluated at four time points: during France’s first lockdown (April–May 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 50 publications
2
11
0
1
Order By: Relevance
“…Laurinaitytė et al [ 17 ] studied the association between health risk behaviors and mental health among Lithuanian university students during this pandemic. In addition, studies have shown that persistent loneliness and social isolation have adverse effects on the mental health of college students [ 18 ]. Investigating the determinants of mental health during the COVID-19 pandemic from different perspectives was necessary, but little attention had been paid to the effect of income on mental health.…”
Section: Introductionmentioning
confidence: 99%
“…Laurinaitytė et al [ 17 ] studied the association between health risk behaviors and mental health among Lithuanian university students during this pandemic. In addition, studies have shown that persistent loneliness and social isolation have adverse effects on the mental health of college students [ 18 ]. Investigating the determinants of mental health during the COVID-19 pandemic from different perspectives was necessary, but little attention had been paid to the effect of income on mental health.…”
Section: Introductionmentioning
confidence: 99%
“…Respondenci na etapie trzeciej tury byli objęci daleko idącymi obostrzeniami oraz przytłoczeni znaczącą ilością informacji przekazywanych przez media już od ponad 4 miesięcy, co umożliwiło analizę pod kątem długotrwałego stresu. Było to trafne wnioskowanie, ponieważ badania z 2022 roku potwierdzają, że napięcie i negatywne sposoby jego zwalczania nasilają się wraz z czasem trwania pandemii [21].…”
Section: Materiał I Metodyunclassified
“…Although affect and emotion regulation abilities seem to have been important determinants of emotional trajectories and adaptiveness during lockdown (e.g., Gullo et al, 2020 ; Lábadi et al, 2021 . ; Park et al, 2021 ; Smith et al, 2020 ; Wang et al, 2020 ; Zsido et al, 2022 ), there has been little research on affective dynamics and longitudinal changes across successive lockdowns ( Charbonnier et al, 2022 ). The psychological consequences of lockdown are many and complex, owing to the numerous dynamic interactions between the public health situation, affect, and emotion regulation strategies ( Martín-Brufau et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%